الذكاءت المتعددة با التقييم وتطبيق فى التعليم اللغة العربية (الذكاءت الموسيقي،المخابرات الشخصية، بين الشخصية الطبعي): Multiple Intelligence Assessment and Application in Arabic Language Education (Musical Intelligence, Interpersonal Intelligence, and Natural Personality) - Puti Rindang Sari; Dewi Chamidah (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
مستخلص البحث: تمتلك الذكاءات المتعددة أنواعًا مختلفة من الذكاء، ستتم مناقشة أربعة منها وهي الذكاء الموسيقي، والذكاء الشخصي، والذكاء الشخصي، والذكاء الطبيعي. تستخدم هذه الدراسة طريقة نوعية باستخدام استراتيجية دراسة الأدب. البيانات التي تم الحصول عليها من الملاحظة وقراءة الكتب المتعلقة بالذكاءات المتعددة والتوثيق. تعتبر نتائج دراسة الذكاءات المتعددة مفهومًا استثنائيًا للغاية اليوم، حيث لا يهتم الأطفال فقط بالدرجات العالية، ولكن يمكنهم أيضًا رؤية أن الطفل لديه مزايا خاصة به وفقًا لذكاءاتهم المتعددة. في هذه الذكاءات المتعددة يوجد تطبيقها في كل مهارة لتعلم اللغة العربية. الذكاءات المتعددة نفسها لها طريقتها الخاصة في تقييم أو تقييم الطريقة الصحيحة لكل ذكاء مرتبط بكل مهارة بالإضافة إلى تدريب المثابرة والمهارات والتعاون للطلاب. الكلمات الأساسية: الكلمة، الذكاءت المتعددة، التقييم، اللغة العربية. Abstract: Multiple intelligences have different types of intelligence, four of which will be discussed: musical intelligence, intrapersonal intelligence, intrapersonal intelligence, and naturalistic intelligence. This study uses a qualitative method using a literature study strategy. Data obtained from observation, reading books related to multiple intelligences, and documentation. The results of the study of multiple intelligences are a very extraordinary concept today, as children are not only interested in high grades, but they can also see that the child has their own advantages according to their multiple intelligences. In these multiple intelligences there is an application in every skill for learning the Arabic language. Multiple intelligences themselves have their own way of assessing or evaluating the correct way for each intelligence associated with each skill as well as training students' perseverance, skills and cooperation. Keywords: Word, Multiple intelligences, evaluation, Arabic Language